ICOS ATC 14C Release analysed by ICOS CRL from Hyltemossa (150.0 m), 2015-09-23–2025-10-21 - Michal Heliasz; Tobias Biermann (Integrated Carbon Observation System, 2026)
The ICOS Central Radiocarbon Laboratory (CRL) central task is the high-precision measurement of the ¹⁴C content in atmospheric CO₂. The ¹⁴CO₂ activity is determined for grab samples (flask) as well as for two-week integrated ambient air samples. Two ¹⁴CO₂ analytical techniques are applied in the CRL: Accelerator Mass Spectrometry (AMS) in collaboration with the CEZA laboratory in Mannheim, Germany (Lux, 2019), and Low-Level gas proportional Counting (LLC) (Kromer & Münnich, 1992). The comparability of both measurement techniques is continuously monitored and was documented in Hammer et al. (2017)
Lux, J. T. (2018). A new target preparation facility for high precision AMS measurements and strategies for efficient ¹⁴CO₂ sampling (Doctoral dissertation). DOI: https://doi.org/10.11588/heidok.00024767
Kromer, B., & Münnich, K. O. (1992). CO₂ gas proportional counting in radiocarbon dating—review and perspective. Radiocarbon after four decades, 184-197. DOI: https://doi.org/10.1007/978-1-4757-4249-7_13
Hammer, S., Friedrich, R., Kromer, B., Cherkinsky, A., Lehman, S. J., Meijer, H. A., ... & Uchida, M. (2017). Compatibility of Atmospheric ¹⁴CO₂ Measurements: Comparing the Heidelberg Low-Level Counting Facility to International Accelerator Mass Spectrometry (AMS) Laboratories. Radiocarbon, 59(3), 875-883. DOI: https://doi.org/10.1017/RDC.2016.62
See also CEZA laboratory: https://www.ceza.de/en
Heliasz, M., Biermann, T. (2026). ICOS ATC 14C Release analysed by ICOS CRL from Hyltemossa (150.0 m), 2015-09-23–2025-10-21, ICOS RI, https://hdl.handle.net/11676/39TfcI2s79edGFeREGKVIcu8
Keywords: Atmosphere Thematic Centre; 14CO2; ICOS; time instant, UTC; time instant, UTC; integration time; integration time; Δ14C; Δ14C; weighted standard error of Δ¹⁴C; weighted standard error of Δ¹⁴C; number of points; number of points; quality flag; quality flag; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap